Dimethyl 4,4′-dihydroxy-3,3′-{[(3aRS,7aRS)-2,3,3a,4,5,6,7,7a-octahydro-1H-1,3-benzimidazole-1,3-diyl]bis(methylene)}dibenzoate - Rivera, Augusto (International Union of Crystallography, 2011)
The title compound, C(25)H(30)N(2)O(6), has the imidazolidine ring in an envelope conformation. There are two intramolecular O—H⋯N hydrogen-bond interactions with graph-set motif S(6). The cyclohexane ring adopts a slightly distorted chair conformation. One methyl carboxylate substituent forms a dihedral angle of 12.00 (5)° with the plane of the benzene ring, while the other methyl carboxylate group is almost coplanar, making a dihedral angle of 2.26 (9)°. In the crystal, pairs of intermolecular C—H⋯O hydrogen bonds form racemic dimers, corresponding to an R (2) (2)(18) graph-set motif. Further weak C—H⋯O interactions generate a chain running along the c axis.